The estimation of new isolates of the Pleurotus ostreatus (Jacq.: Fr.) Kummer fungus using of infrared spectroscopy - Дорошкевич, Н. В.; Шевкопляс, В. М. (Scientific Progress & Innovations, 2012)
In this work a preliminary estimation of new strains of the P. ostreatus using IR-spectroscopy extracellular protein has been made. It is shown that the adsorption band at 3350, 2920, 1410, 1300–1000, 925–850 and 690–600 sm-1 indicate that various functional groups take place. Data IR-spectroscopy indicates that optical density of adsorption has different intensity and it is as result of physiological particularities studied strains. It is shown that an adsorption band at 1040 sm-1 characterizes at present within extracellular proteins of active oxygen, which participates in a destruction of the nutrient medium carbon. The intensity of adsorption band at 1040 sm-1 may be used for additional estimation of physiological activity of the fungus. The relationship between accumulation biomass of new isolates at fluid nutrient medium and intensity of adsorption band.